Kedudukan Jaminan Perlindungan Terhadap Anak Diluar Perkawinan Ditinjau dari Konsep Hak Asasi Manusia: Position the Guarantee of Protection for Children Outside Marriage in Terms of Concept Human Rights - Rahmi Anisa; Ardiansah Ardiansah; Bahrun Azmi (DOKTRINA: JOURNAL OF LAW, 2022)
A child is born from the result of a legal marriage between his parents. According to Article 1 paragraph (1) of Law Number 1 of 1974 it is stated that "marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the One Godhead". It is known that marriage is something that must be done by both partners who like each other. Marriage can justify a biological relationship between a man and a woman to produce offspring so that a household can be upheld and fostered in accordance with religious norms and community life systems. The problem in this study is that in law the status of children is recognized in 2 ways, namely firstly the status of a legitimate child due to a legal marriage and secondly the status of a child due to an illegitimate/betelling marriage. born out of wedlock. This research is a normative legal research. The results of the study of this research are that the legal basis and regulations have been found that since the Constitutional Court Decision Number: 46/PUU-VIII/2010 has made the status of both legal children and children born out of wedlock equal. and this is in accordance with the principle of equality before the law and in line with the 1945 Constitution in particular Article 28.